(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
There is no denying in the fact that “woman subject” has been prominentin Kamala Markandaya’s novels, as women play an important part. In depictingwomen and their problems, the novelist exhibits signs of deep impact of afeminist school of writing. Women have significant place in Kamala Markandaya’snovels. Her presentation of feminine perception is directed towards anobjective account of women’s emotions, assessing Indian womanhood’sconfrontation with male reality. There is no overstatement in calling hernovels as feminine as they be a sign of more the world of women and their waysof life then the world of men.